Relationship Between the Use of Mobile Online Registration for National Health Insurance (NHI) Outpatients with Patient Waiting Time Satisfaction at Grandmed Hospital Lubuk Pakam in 2025 - Br Ginting, Luci Riani; Ardhana, Ryanthy Arlizha (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patient satisfaction is a key indicator in assessing healthcare service quality and reflects the overall performance of a hospital. Low satisfaction levels may reduce patient visits and impact service sustainability. Several factors influence satisfaction, including healthcare workers’ attitudes, communication effectiveness, and service efficiency. In medical record services, outpatient registration often faces issues such as long queues, extended waiting times, and limited access to doctor schedules. To address these problems, BPJS Kesehatan introduced the Mobile JKN application, which allows online outpatient registration. However, its utilization at Grandmed Lubuk Pakam Hospital remains limited due to technical barriers, quota distribution issues, and insufficient socialization. This study employed an analytical quantitative approach with a cross-sectional design to evaluate the relationship between Mobile JKN utilization and patient satisfaction with waiting time. The study was conducted from December 2024 to May 2025 with a total population of 6,737 outpatients. A sample of 124 respondents was determined using the Stanley Lameshow formula and selected through purposive sampling. Data were collected using questionnaires and analyzed with the Chi-Square test at a 95% confidence level (α = 0.05). Findings revealed that 54.1% of respondents rated the online registration as good, and 52.4% reported satisfaction with waiting times. The Chi-Square test produced a p-value of 0.037, indicating a significant relationship between Mobile JKN usage and patient satisfaction. In conclusion, higher utilization of Mobile JKN is associated with greater patient satisfaction regarding outpatient waiting times.